THE IMPLEMENTATION OF RESTORATIVE JUSTICE FOR NARCOTICS ADDICTS BASED ON LEGAL BENEFITS - Amalia Nugraheni, Novie (Jurnal Pembaharuan Hukum, 2024)
Narcotics addicts are "self victimizing victims", because narcotics addicts suffer from dependence syndrome as a result of their own narcotics abuse. The purpose of writing this article is to analyze the current law enforcement against narcotics addicts and the implementation of restorative justice for benefit-based narcotics addicts. This type of legal research is normative juridical research. Crimes related to narcotics include special crimes, where the provisions used include special provisions of the law. Narcotics crimes are called special crimes, because narcotics crimes do not use the Criminal Code (KUHP) as the basis for regulation, but use Law No. 35 of 2009 concerning Narcotics. Narcotics addicts and victims of narcotics abuse are not solely seen as perpetrators of criminal acts, but also as victims, where the implementation of rehabilitation is part of an alternative punishment. The drug users as victims of narcotics crimes must be restored / cured and not to be imprisoned. Restorative justice for drug users can save their future. Even though their past and present have been lost as a result of the drug abuse.